Classical sociological theory : rediscovering the promise of sociology - Goodwin, Glenn A.; Scimecca, Joseph A. (Belmont, CA : Thomson/Wadsworth, 2006)
[This book] reflects sixty-plus years of experience teaching required undergraduate and graduate courses on classical sociological theory. It is a subject matter that both [authors] continue to feel passionately about, and one that [they] feel currently lakcs a text that can both create a similar passion for classical theory in students and present the substantive ideas of the founding men and women of sociology.... [This] text overcomes these limitations. -Pref.
Includes bibliographical references and index
Keywords: Sociology -- History; Sociology -- Methodology -- History; Sociologists -- Biography